2014
DOI: 10.4103/2319-4170.126447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flaxseed formulation as a potential therapeutic agent in mitigation of dyslipidemia

Abstract: The supplementation of roasted flaxseed powder for 3 months improved the BMI, blood pressure, and lipid profile of dyslipidemic subjects, thus exhibiting cardio protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
5
16
0
2
Order By: Relevance
“…Our results confirmed the previous data [28], which showed that flaxseed powder consumption desirably reduced serum lipids. Similar to our results, a recent study reported that flaxseed intake is associated with a significant improvement in lipid profile [29]. Cornish et al found only reduction in serum TG and not the cholesterol level of patients with metabolic syndrome who were supplemented with flaxseed lignin [30].…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed the previous data [28], which showed that flaxseed powder consumption desirably reduced serum lipids. Similar to our results, a recent study reported that flaxseed intake is associated with a significant improvement in lipid profile [29]. Cornish et al found only reduction in serum TG and not the cholesterol level of patients with metabolic syndrome who were supplemented with flaxseed lignin [30].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, 1,698 participants were assigned into these trials randomly, in that 875 individuals were allocated to the flaxseed intervention group and 823 to the control group. The 31 randomized controlled trials (RCTs) were published from 1993 to 2020, and were conducted in China (n = 3) [ 19 , 28 , 29 ], United States (n = 6) [ 21 , 23 , 30 33 ], Canada (n = 3) [ 34 36 ], Japan (n = 1) [ 20 ], Greece (n = 3) [ 37 39 ], Brazil (n = 5) [ 22 , 40 – 43 ], Demark (n = 1) [ 44 ], Germany (n = 1) [ 45 ], India (n = 1) [ 46 ], and Iran (n = 7) [ 47 53 ]. Four trials were conducted exclusively in men [ 20 , 37 39 ], 2 trials were conducted in women [ 31 , 44 ], the remaining 25 RCTs were conducted in both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, the most effective plants on the weight loss are green tea (with effective dose of 6,000 mg/day for green tea and 400-800 mg/day for catechins), P. vulgaris (with effective dose of 1,000 mg/day), G. cambogia (with effective dose of 2,400 mg/day), N. sativa (with effective dose of 3,000 mg/day), puerh tea (with effective dose of 1,000 mg/day), I. gabonensis (with effective dose of 300 mg/day), C. fimbriata (with effective dose of 1,000 mg/day), respectively. Other plants that have been affected by weight loss and BMI include cumin (with doses of 100 and 3,000 mg/day; Zare, Heshmati, Fallahzadeh, & Nadjarzadeh, 2014, Taghizadeh, Memarzadeh, Asemi, & Esmaillzadeh, 2015, flaxseed (with doses of 2,500 and 6,000 mg/day; Saxena & Katare, 2014, Cassani, Fassini, Silvah, Lima, & Marchini, 2015, Hibiscus sabdariffa (with effective dose of 75 mg/day; Kuriyan, Kumar, Rajendran, & Kurpad, 2010, Chang, Peng, Yeh, Kao, & Wang, 2014, rosehip (with dose of 100 mg/day; Nagatomo et al, 2015, Andersson, Berger, Hogberg, Landin-olsson, & Holm, 2012, Lycium Barbarum (with doses of 30, 60, and 120 ml/day; Amagase & Nance, 2011, Amagase & Nance, 2008), cinnamon (with doses of 550 and 2,000 mg/day; Vafa et al, 2012, Akilen, Tsiami, Devendra, & Robinson, 2010, and so forth, as detailed in Table S3.…”
Section: Body Weightmentioning
confidence: 99%